ANALISIS FINANSIAL USAHA PETERNAKAN PEMBIBITAN SAPI POTONG RAKYAT DI DAERAH PERTANIAN LAHAN KERING : Studi Kasus di Wilayah Kecamatan Semin, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Eka Handayanta; Endang Tri Rahayu; Muji Sumiyati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
The purpose of this study was to determine the financial feasibility and break even point on the cattle's breeding  farms. Taking place in  the three sites in the rural areas with the highest, moderate and lowest on population of beef cattle, such as  villages of Kemejing, Candirejo , and  Pundungsari all of them  in the district of Semin, Gunung Kidul regency, Yogyakarta. This study was conducted in September up to October 2011. The  using methode of survey to collect primary data from 60 farmers respondents and secondary data from relevant agencies. Sample was determined by purposive sampling. Financial analysis of the cattle's breeding farms using investment criteria such as a benefit cost ratio (BCR), net present value (NPV), internal rate of return (IRR), payback period of credit (PPC), and the break even point (BEP) based on 8 years investment with a discount factor of 12% per year. The analysis showed that the BCR value of 1.61; NPV of   12.308.146,72; IRR of 23.40%; PPC for 4.53 years and the BEP value is based on sales amounted to Rp 25,991,672.10 or based on 6 heads of animal units. The conclusion of this study is a cattle's breeding farms in dryland farming areas are eligible to run with BEP on 6 heads of beef cattle